Reformulação por paráfrase e por correção no processo de produção textual de artigo de opinião - Burato, Thais Aparecida (2019)
The production of texts appropriate to each communicative situation has undeniable importance, but this does not always occur. Often the lack of prior knowledge about the genre of discourse that is most acceptable for each moment causes communication failures. Therefore, the present work deals with the process of textual production and focuses on the article of opinion, which is part of the argumentative sphere and enables the writer to express his point of view. The main objective was to study the process of construction and reconstruction of the text, analyzing each stage of production. Through this, it was possible to verify how the paraphrase and the correction act in the moments of writing. The articles of opinion produced by students of the third year of a state college in the city of Pato Branco – Paraná, who participated in the extension course "Workshop of reading, writing and rewriting of opinion articles" in its sixth edition were analyzed. the analysis was performed using the theories of Hilgert and Barros (1999), Bakhtin (2003), Lima (2013), among others. The first one was used to present and produce the diagnostic text of each student.This first text did not have the guidance of the teachers, it only presents the previous knowledge that each student had In the following meetings, the students had to return their texts and received guidelines on the characteristics of g Based on this, they produced four other versions with the same theme and one last opinion article with a different theme. After analyzing the data, it was possible to conclude that the most important reformulations are the correction, at times of changing the course of writing, and the paraphrase, when the article reaches a relatively stable form. Therefore, the correction changes the direction of the argumentation and of the whole construction of the text, since the paraphrase maintains the same idea dictated with different words. Anyway, anyone who is learning to write the genre of opinion articles regulates their language until they reach a desired level to persuade their readership.